Integration of academic and artistic work - Malene Hauxner (Projets de Paysage)
The following is an attempt to describe an academic method for the analysis of urban landscapes with the aim of defining architectural problems and significance. It is done through contextual reading of the architectural language. This process is seen as the opposite of the artistic, to arrive at the language of the work from the architectural problem. Every project begins with formulation of the problem and the questions. This applies both in preparing an academic analysis and in preparing an artistic project. These two tasks could and should be seen as connected. Both require research into existing knowledge, determination of theory and background and choice of analytical or artistic method as well as evaluation and conclusion. Both genres, the academic analysis and the artistic project, concern argumentation and documentation of an investigation, of a professional problem. The purpose of analyzing landscape architecture is thus both to learn, understand, recognize and experience - and create spaces and works. In order to say anything sensible about urban landscape and its landscape architecture, whether the aim is to understand, recognize and develop the artistic experience or to transform, improve and renew it, one must define the landscape-architectural, architectural, and artistic problem.